2019
DOI: 10.3390/nu11081823
|View full text |Cite
|
Sign up to set email alerts
|

Choline: Exploring the Growing Science on Its Benefits for Moms and Babies

Abstract: The importance of ensuring adequate choline intakes during pregnancy is increasingly recognized. Choline is critical for a number of physiological processes during the prenatal period with roles in membrane biosynthesis and tissue expansion, neurotransmission and brain development, and methyl group donation and gene expression. Studies in animals and humans have shown that supplementing the maternal diet with additional choline improves several pregnancy outcomes and protects against certain neural and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 102 publications
(141 reference statements)
0
95
0
Order By: Relevance
“…Therefore, this raises concerns and questions about whether choline dietary guidelines require revision. Thus, in the meantime, as concluded by Korsmo et al (2019) [69], the consumption of 450-1000 mg choline/day appears to be a suitable intake level that would support fetal brain function and neurodevelopment, alongside other pregnancy outcomes. Finally, from here on, it is important to impart ongoing awareness to healthcare professionals, including midwives, obstetricians, and pediatricians about the importance of choline across the first 1000 days of life.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, this raises concerns and questions about whether choline dietary guidelines require revision. Thus, in the meantime, as concluded by Korsmo et al (2019) [69], the consumption of 450-1000 mg choline/day appears to be a suitable intake level that would support fetal brain function and neurodevelopment, alongside other pregnancy outcomes. Finally, from here on, it is important to impart ongoing awareness to healthcare professionals, including midwives, obstetricians, and pediatricians about the importance of choline across the first 1000 days of life.…”
Section: Discussionmentioning
confidence: 95%
“…Growing evidence indicates that choline supply may favorably influence functional processes of the placenta, including angiogenesis, inflammation, and macronutrient transport [69]. A 12-week trial which randomized 26 healthy pregnant women to take 480 mg or 930 mg/day choline for 12-weeks from 26-29 weeks gestation showed that there was statistically significant (30%) down-regulation of the antiangiogenic factor and preeclampsia risk marker fms-like tyrosine kinase-1 in the placenta tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choline is a versatile semi-essential nutrient contained in eggs, meat, beans, and other foods. It participates in lipid metabolism, membrane structure maintenance, methyl group donation, and cellular signaling [3]. Research has shown that choline supplementation during pregnancy alters fetal epigenetic programming, improves offspring cognitive development, and modifies placental vasculature and macronutrient transport in rodents or humans [3].…”
Section: Introductionmentioning
confidence: 99%
“…It participates in lipid metabolism, membrane structure maintenance, methyl group donation, and cellular signaling [3]. Research has shown that choline supplementation during pregnancy alters fetal epigenetic programming, improves offspring cognitive development, and modifies placental vasculature and macronutrient transport in rodents or humans [3]. We previously reported that choline supplementation during pregnancy prevented fetal overgrowth and alleviated excess adiposity in high-fat (HF) fed mouse dams that were obese and glucose intolerant [4,5].…”
Section: Introductionmentioning
confidence: 99%